IDENTIFIKASI KUALITAS AIR LAUT PANTAI SADRANAN, KABUPATEN GUNUNGKIDUL, YOGYAKARTA - Agry, Firdausa Putra; Erzad, Avisha Fauziah; Octoriani, Widyanti (Universitas Teuku Umar, 2025)
Water quality is one of the indicators of tourists' interest in visiting a beach area. Sadranan Beach is one of the beaches in the south coast area that is attracted by tourists because it has the beauty of beach tourism such as white sand, diversity of marine life and relatively low sea waves. This study aims to analyze the quality of Sadranan Beach seawater using the storet method. The research method used purposive sampling with 10 sampling points with a distance of 10 meters from each sample point. Measurement of water quality parameters carried out are physical and chemical parameters which are then compared with seawater quality standards to determine the value of the storet method so that the category of water quality pollution in Sadranan Beach is known. Based on the research that has been done, the values of physical and chemical parameters of water quality studied are temperature ranging from 30 0C - 31.5 0C, turbidity ranging from 0 NTU - 3.32 NTU, pH ranging from 7.69 - 8.11, DO ranging from 4.51 mg/l - 6.27 mg/l, and salinity 30.55 ppt - 34.9 ppt. The results of the analysis with the STORET method show that the water quality at Sadranan Beach, Gunungkidul Regency, Yogyakarta for marine biota and marine tourism is in category B mild pollution with scores ranging from -8 and -2.